Schneeballschlachtenspiel as Automation Excercise in German Teaching - Rofi'ah Rofi'ah; Herri Akhmad Bukhori (Universitas Negeri Malang, 2020)
This study aimed at describing the use of “Schneeballschlachtenspiel” as “Automatisierungsübung” or automation excercise for student in German lteaching. This is a qualitative study that has been supported by quantitative data. The data were the use of Schneeballschlachtenspiel during the teaching which was collected through observation as well as documentation and learners’ perceptions about Schneeballschlachtenspiel which were collected through questionnaire. The data source were students of the German Department at Universitas Negeri Malang who were attending the course Deutsch 3. The result of the study show that Schneeballschlatenspiel as active-passive sentence exercise works well in the class. The students find that it was fun during the game and they have positive mind about it. Schneeballschlachten help them understand paricular grammar and they will use it again. In addition, the students find it interresting and attractive.